2015
DOI: 10.3390/rs70100600
|View full text |Cite
|
Sign up to set email alerts
|

The Ground-Based Absolute Radiometric Calibration of Landsat 8 OLI

Abstract: This paper presents the vicarious calibration results of Landsat 8 OLI that were obtained using the reflectance-based approach at test sites in Nevada, California, Arizona, and South Dakota, USA. Additional data were obtained using the Radiometric Calibration Test Site, which is a suite of instruments located at Railroad Valley, Nevada, USA. The results for the top-of-atmosphere spectral radiance show an average difference of −2.7, −0.8, 1.5, 2.0, 0.0, 3.6, 5.8, and 0.7% in OLI bands 1-8 as compared to an aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
93
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(101 citation statements)
references
References 42 publications
3
93
0
5
Order By: Relevance
“…It is important to study continuity among sensors from the same series of satellites by considering of the important parameters including sensor characteristics, over-pass time, scanning system, angular affect and etc. A few studies related to the continuity of Landsat 8 have been conducted, including preflight and post-launch calibrations [28][29][30][31][32][33]. Most of these studies have shown that the continuity between the Landsat-8 OLI and Landsat-7 ETM+ is good.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to study continuity among sensors from the same series of satellites by considering of the important parameters including sensor characteristics, over-pass time, scanning system, angular affect and etc. A few studies related to the continuity of Landsat 8 have been conducted, including preflight and post-launch calibrations [28][29][30][31][32][33]. Most of these studies have shown that the continuity between the Landsat-8 OLI and Landsat-7 ETM+ is good.…”
Section: Introductionmentioning
confidence: 99%
“…3% in the middle of the visible portion of the spectrum [21]. In this work, as can been seen in Table 6, the uncertainty in the TOA Radiance predicted by MODTRAN ranged from 3.1% to 4.4% in the four MUX and WFI spectral bands.…”
Section: Resultsmentioning
confidence: 54%
“…For ETM+/Landsat-7, TM/Landsat 4 and 5, for example, the sites were a rectangular area that is 480 by 120 m [10]. The size of one site used to calibrate the OLI/Landsat-8 was 100 by 250 m [21]. Here, a 160 by 300 m surface was selected, which is appropriate size to calibrate sensors on-board CBERS-4 (or better ground spatial resolution).…”
Section: Surface Reflectancementioning
confidence: 99%
“…Therefore, in-orbit vicarious calibration must be used to transform the satellite data into meaningful physical information. Previous studies used reflectance-, irradiance-, and radiance-based techniques [2,3] to successfully calibrate satellites such as the SPOT HRV [4], Landsat TM/ETM [3,5,6], Airborne Visible and Infrared Spectrometer [7], EO-1 Hyperion [8,9], and FY [10,11], MISR [12], Landsat OLI [13], CBERS-4 [14], and many other optical remote sensors [15]. The reflectance-and irradiance-based methods have been compared with cross-calibration methods to derive the calibration coefficients for the BJ-1 microsatellite [16].…”
Section: Satellite Characteristic Descriptionmentioning
confidence: 99%